UNDERSTANDING OF NATIONAL IDENTITY ON VASYLSHKLIAR’S “ZALYSHENETS. BLACK RAVEN” - Ушневич, С. Е. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article investigates the specifics of the author’s thinking in the light of alternative modeling history in the novel environment; proanalizuvano question of identity of people in a local environment; attempt to understand the dominant ethno-national in art fabric piece.